A pocket style manual : APA version - Hacker, Diana, ....-; Sommers, Nancy, ....-; Matthews, Rick A., ....- (Boston (Mass.) : Bedford/St. Martin's, 2020)
The eighth edition of A Pocket Style Manual, APA Version, covers everything you need for writing in college courses such as psychology, sociology, criminal justice, nursing, education, business, composition, and more. New step-by-step advice applies to writing assignments in any course. There's also new advice for avoiding plagiarism, paraphrasing, and evaluation online sources. When you add all that great new help to Pockets' tested, trusted grammar and style advice plus documentation models in APA style, you've got the most powerful pocket guide for writing and research.
Keywords: Eindwerken; Hoger onderwijs; Literatuuronderzoek; Hoger onderwijs; bronvermelding; Hoger onderwijs; onderzoeksvaardigheden; Hoger onderwijs; schrijven